Chlorpromazine induced ocular myasthenia gravis - S, Nitya; P, Deepa Kameswari; A, Mangaiarkkarasi; A, Jagadeesh; R, Meher Ali (International Journal of Basic & Clinical Pharmacology, 2017)
Drug induced bilateral ptosis is a very rare adverse drug reaction. Here we report a case of ten year old male child with chlorpromazine induced bilateral ptosis due to ocular myasthenia.